Surveillance transbronchial biopsies in infant lung and heart–lung transplant recipients. (21st August 2013) - Hayes, Don; Baker, Peter B.; Kopp, Benjamin T.; Kirkby, Stephen; Galantowicz, Mark; McConnell, Patrick I.; Astor, Todd L.
Abstract There are limited published data on surveillance TBB for the identification of allograft rejection in infants after lung or heart‐lung transplantation. We performed a retrospective review of children under one yr of age who underwent lung or heart–lung transplant at our institution. Since 2005, four infants were transplanted (three heart–lung and one lung). The mean age (±s.d.) at the time of transplant was 5.5 ± 2.4 (range 3–8) months. A total of 16 surveillance TBB procedures were completed in both inpatient and outpatient settings, with a range of 3–7 performed per patient. A minimum of five acceptable tissue pieces with expanded alveoli were obtained in 81% (13/16) of TBB procedures and a minimum of three pieces in 88% (14/16). There was no evidence of acute allograft rejection in 88% (14/16) of TBB procedures. One TBB procedure yielded two tissue specimens demonstrating A2 acute allograft rejection. One TBB procedure failed to yield tissue with sufficient alveoli. Additionally, B‐grade assessment identified B0 in 50% (8/16), B1R in 12% (2/16), and BX (ungradeable or insufficient sample) in 38% (6/16) of biopsy procedures, respectively. In conclusion, TBB may be safely performed as an inpatient and outpatient procedure in infant lung and heart–lung transplant recipients and may provide adequate tissue for detecting acute allograft rejection and small airway inflammation.